LITERATURE REVIEW: INTERACTIVE MULTIMEDIA FLOWCHART WITH THE HELP OF CHATBOT AI TO IMPROVE THE SELF-REGULATED LEARNING ABILITY OF STUDENTS IN INDONESIA - Fifinella; Andi Mariono; Khusnul Khotimah (RADJA PUBLIKA, 2025)
The development of the Smart Society 5.0 era requires learning innovations that are able to integrate information and communication technology (ICT) into the educational process effectively and ethically. This study aims to analyze the potential and relevance of interactive multimedia flowcharts assisted by AI Chatbots in improving students' self-regulated learning (SRL) skills. This paper uses an analytical literature review approach with two main focuses: (1) defining the concept of interactive multimedia flowcharts assisted by AI chatbots, and (2) examining its influence on students' SRL skills. Data was obtained from various credible scientific sources such as Springer, Taylor & Francis, MDPI, ScienceDirect, and Google Scholar. The results of the study show that interactive flowcharts function as visual tools that help students formulate their thoughts systematically, while AI chatbots act as learning partners that provide personalized and real-time feedback. The combination of the two results in an interactive learning environment that can stimulate student planning, supervision, and self-reflection as the core of the SRL process. Conceptually, the synergy between interactive multimedia design and artificial intelligence is able to strengthen the cognitive, metacognitive, and motivational dimensions of students. Thus, this innovation has the potential to become a digital learning model that supports the development of learning independence, critical thinking, and lifelong learning in the context of higher education in the digital era.